2016
DOI: 10.1063/1.4941537
|View full text |Cite
|
Sign up to set email alerts
|

Low leakage ZrO2 based capacitors for sub 20 nm dynamic random access memory technology nodes

Abstract: During dynamic random access memory (DRAM) capacitor scaling, a lot of effort was put searching for new material stacks to overcome the scaling limitations of the current material stack, such as leakage and sufficient capacitance. In this study, very promising results for a SrTiO3 based capacitor with a record low capacitance equivalent thickness value of 0.2 nm at target leakage current are presented. Due to the material properties of SrTiO3 films (high vacancy concentration and low band gap), which are leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This composition maintains full process compatibility with the CMOS technology . Both oxides are already used in high‐ k metal gate and DRAM processes and can be deposited by the well‐developed atomic layer deposition (ALD) technique. This allows conformal depositions onto 3D structures for state‐of‐the‐art technology nodes…”
Section: Introductionmentioning
confidence: 99%
“…This composition maintains full process compatibility with the CMOS technology . Both oxides are already used in high‐ k metal gate and DRAM processes and can be deposited by the well‐developed atomic layer deposition (ALD) technique. This allows conformal depositions onto 3D structures for state‐of‐the‐art technology nodes…”
Section: Introductionmentioning
confidence: 99%
“…These favorable properties have led to commercial use of ZrO 2 thin films as dielectrics and insulators in a variety of microelectronics applications, such as dynamic random access memory [2], radio-frequency and analog/mixed-signal (RF/AMS) integrated circuits [3,4], and non-volatile resistive random access memory [5]. …”
Section: Introductionmentioning
confidence: 99%
“…To assess the structural properties of the two ZrO 2 layers Grazing Incidence X‐ray diffraction (GI‐XRD) diffraction and scanning electron microscopy (SEM) was performed after the removal of the top electrode ( Figure ). Since simulation results by Materlik et al suggest that the surface energy of the grains has a strong impact on the phase formation, a similar grain radius should result in a similar phase composition. For verification, XRD measurements were performed and compared to the patterns for the monoclinic and tetragonal phases of ZrO 2 (Figure a lower part).…”
Section: Antiferroelectric Properties Of Zro2mentioning
confidence: 99%
“…Metal‐insulator‐metal (MIM) capacitors with TiN electrodes and ZrO 2 /Al 2 O 3 /ZrO 2 (ZAZ) dielectric stacks were applied in commercial DRAM products from the 80 nm node to current 18 nm generations during the last decade . In a study by Pešić et al, it was shown how the existing production type ZAZ layers can be implemented in sub 18 nm nodes.…”
Section: Introductionmentioning
confidence: 99%